Aspirin and clopidogrel treatment impair nitric oxide biosynthesis by platelets - O’Kane, Peter D.; Reebye, Vikash; Ji, Yong; Stratton, Paula; Jackson, Graham; Ferro, Albert (Journal of molecular and cellular cardiology, 2008)
Aspirin and clopidogrel are used therapeutically for their anti-platelet effects. We examined the effects of aspirin and clopidogrel on basal and β-adrenoceptor (β-AR)-mediated platelet nitric oxide (NO) synthesis in healthy subjects and patients with coronary heart disease (CHD). Healthy subjects ( n = 19) were randomized in a double-blind cross-over manner to receive aspirin or clopidogrel, each at 75 mg daily, for 14 days. Patients ( n = 17) of similar age with CHD, taking aspirin, were randomized double-blind to either continue on aspirin 75 mg daily or to receive clopidogrel 75 mg daily for 14 days. NO synthase (NOS) activity was measured from l-[ 3H]arginine to l-[ 3H]citrulline conversion, and cGMP was determined by radioimmunoassay, in platelets basally and following incubation with isoproterenol or albuterol (each at 10 −5 mol/L). In healthy subjects, aspirin did not affect basal NOS activity or cGMP in platelets, but suppressed the normal increase in both by isoproterenol and albuterol. Clopidogrel suppressed platelet NOS activity and cGMP both basally and in response to β-AR agonists. In platelets from CHD patients, clopidogrel suppressed basal and β-AR-stimulated NOS activity and cGMP as compared with aspirin. Platelet NOS activity and cGMP were lower in CHD subjects pre-randomization compared with healthy subjects both pre-randomization and post-aspirin. We conclude that chronic aspirin treatment suppresses β-AR-stimulated but not basal platelet NO synthesis, as previously described, whereas chronic clopidogrel treatment suppresses both, with resultant functional consequences. Moreover, CHD may itself be associated with decreased platelet NO biosynthesis.